(untitled) (Research, Society and Development, 2019)
The present research aims to analyze how affection existent in the professor-student relation can come to contribute or hinder the process of learning mathematics. Affection is one of the most important elements in overcoming adversities in the educative process, whether it is in school or out of it, and especially between the professor and the student. We had the participation of 33 university students that are majoring in Mathematics in a public institution, in order to search for answers to our question (How does the professor-student relationship can come to contribute or hinder the process of learning mathematics in higher education students?). We used questionnaires and class observation as data production instruments. Among the findings, we point out the students’ understanding, who considered emotion as essential in overcoming barriers in the academic context.